Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1541-4337.2011.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and Technical Aspects of Yogurt Aroma and Taste: A Review

Abstract: Yogurt is a basic dairy product that has been consumed for centuries as a part of the diet, even when its beneficial effects were neither fully known nor scientifically proven. With time, yogurt has been continuously modified to obtain a product with better appeal and nutritional effects. The flavor components of yogurt are affected because of these modifications. The present review article is focused on the influence of the different parameters and modifications on aroma and taste components of yogurt. Extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
154
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(174 citation statements)
references
References 103 publications
6
154
0
2
Order By: Relevance
“…Similarly, Xanthopoulos et al (2001) observed the reduction of acetaldehyde in some S. thermophilus strains during fermented milk storage. Moreover, diacetyl, mainly produced by S. thermophilus, is another antibacterial compound potentially contributing to the yogurt aroma (Chammas et al, 2006;Kang and Fung, 1999;Routray and Mishra, 2011). In our study, IMAU80846 produced the highest content of diacetyl of 9.79 µg g -1 after storing for 36 h along with a decrease of the viable counts.…”
Section: Changes In Acetaldehyde Diacetyl Lactic Acid and Formic Acmentioning
confidence: 60%
See 1 more Smart Citation
“…Similarly, Xanthopoulos et al (2001) observed the reduction of acetaldehyde in some S. thermophilus strains during fermented milk storage. Moreover, diacetyl, mainly produced by S. thermophilus, is another antibacterial compound potentially contributing to the yogurt aroma (Chammas et al, 2006;Kang and Fung, 1999;Routray and Mishra, 2011). In our study, IMAU80846 produced the highest content of diacetyl of 9.79 µg g -1 after storing for 36 h along with a decrease of the viable counts.…”
Section: Changes In Acetaldehyde Diacetyl Lactic Acid and Formic Acmentioning
confidence: 60%
“…Therefore, screening for Study on Streptococcus thermophilus isolated from Qula and associated characteristic of acetaldehyde and diacetyl in their fermented milk (Received March 3, 2014;Accepted January 9, 2015) Musu Zha, 1 Jie Yu, 1 Yong Zhang, 1 Hongmei Wang, 1 Na Bai, 1 Yanting Qin, 1 De Liangliang, the specific strains which produce the typical flavor of the traditional dairy products is of high importance. Various volatile bacterial metabolites produced by lactic acid fermentation or other related reactions contribute to the flavor of fermented milk products (Routray and Mishra, 2011). For starter cultures, one important evaluating parameter is their aroma-producing ability, which can result from the formation of metabolites such as acetaldehyde and diacetyl (Yuguchi et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Different additives like: sweeteners, fl avourings, fruits, preserves etc. modify the fl avour of yoghurt (Routray and Mishra, 2011). Flavour defects may occur in yoghurts due to prolonged fermentation (too acidic) or insuffi cient fermentation (bland), excessive proteolysis (bitterness), microbiological contamination (yeasty, fruity, musty, cheesy, bitter or soapy-rancid off-fl avours), too low incubation temperature or imbalanced growth of starter bacteria (too little of characteristic fl avour) or off-fl avours in milk base (Walstra et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the flavour score of experimental CSY samples could be attributed to the production of varied flavouring components as a result of their metabolic activity. Each strain of starter culture influences the flavor characteristics of yogurt/ dahi [23]. Even the tartness of the three CSY samples was slightly different; the product having higher acidity was preferred by the judges, possibly because the sugar-acid blend in such product was properly balanced.…”
Section: Flavourmentioning
confidence: 99%
“…18, 21 min), the desired flavour notes of product were subdued. The association of milk constituents in the gelled fermented product, which in turn affects the product's consistency, has a bearing on its flavor perception [23]. Bhattacharya et al [1] reported that Bhapa dahi made using steaming time of 10 to 25 min.…”
Section: Flavourmentioning
confidence: 99%